Combined TOA/DOA for location estimation in MIMO system - Awang Md Isa, Azmi; Haron, Nor Zaidi; Mohamad Isa, Mohd Sa'ari; Mohd Zin, Mohd Shahril Izuan; Zakaria, Zahriladha (Universiti Teknologi Malaysia, 2014)
This paper proposes on the development of a combined location and positioning (L&P) system by combining range measurements and angle measurements for a multiple input multiple output (MIMO) system. The proposed combined technique called as hybrid multiple linear lines of position (HMLLOP) algorithm extends the fundamental idea of using the multiple linear lines of position (MLLOP) scheme when extra information in the form of direction of arrival (DOA) measurements at a minimum of three base stations (BSs) is available. The technique explores the use of multiple lines of position (LOP) instead of circular LOP and determines new lower and upper bounds of DOA according to the measurements obtained from an MLLOP scheme which aims to minimize the DOA error caused by non-line of sight (NLOS) propagation. Simulation results have been provided that show that the proposed combined schemes outperform the range-only algorithm in terms of estimated location accuracy. It has been shown that time of arrival (TOA)-based location can be employed as a baseline location estimation technique, with additional DOA measurements being used to further improve accuracy.